Answer with explanation:
We are asked to prove by the method of mathematical induction that:
3n(n+1) is divisible by 6 for all positive integers.
![3n(n+1)=3* 1(1+1)\\\\i.e.\\\\3n(n+1)=3* 2\\\\i.e.\\\\3n(n+1)=6](https://img.qammunity.org/2020/formulas/mathematics/college/u10aw68wsgyocloq33kunlmnlrzx3egbr4.png)
which is divisible by 6.
Hence, the result is true for n=1
- Let the result is true for n=k
i.e. 3k(k+1) is divisible by 6.
- Now we prove that the result is true for n=k+1
Let n=k+1
then
![3n(n+1)=3(k+1)* (k+1+1)\\\\i.e.\\\\3n(n+1)=3(k+1)(k+2)\\\\i.e.\\\\3n(n+1)=(3k+3)(k+2)\\\\i.e.\\\\3n(n+1)=3k(k+2)+3(k+2)\\\\i.e.\\\\3n(n+1)=3k^2+6k+3k+6\\\\i.e.\\\\3n(n+1)=3k^2+3k+6k+6\\\\i.e.\\\\3n(n+1)=3k(k+1)+6(k+1)](https://img.qammunity.org/2020/formulas/mathematics/college/awmj047jy8o8eadgkagprhmw4yjnieu7lg.png)
Since, the first term:
is divisible by 6.
( As the result is true for n=k)
and the second term
is also divisible by 6.
Hence, the sum:
is divisible by 6.
Hence, the result is true for n=k+1
Hence, we may say that the result is true for all n where n belongs to positive integers.